Application of a Color-Changeable Chewing Gum for Measuring Masticatory Performance of Complete Denture Wearers - Takahashi, Yasuki; Hayakawa, Iwao; Hirano, Shigezo; Watanabe, Ikki; Wu, Chun-Ho (Nihon Hotetsu Shika Gakkai Zasshi, 2001)
Purpose: A color-changeable chewing gum was developed as a simple method to evaluate masticatory ability. The purpose of this study was to determine the capability of the chewing gum to measure masticatory performance of complete denture wearers. Methods: Twenty-seven edentulous patients, who wore newly fabricated complete dentures, volunteered to participate in this study. One month after the completion of denture adjustments, the following experiments were performed. The subjects chewed the color-changeable chewing gum until the color changed completely to red. The gradation of the color was checked by a dentist at every five chewing strokes. The number of chewing strokes at the completion of the color gradation was confirmed, using the color scale for the color-changeable chewing gum, and recorded. Masticatory performance was also obtained using the sieving test reported by Manly and Braley. Spearman's correlation coefficient, between the number of chewing strokes and masticatory performance, was calculated and statistically analyzed. Results: Mean values and standard deviations of the number of chewing strokes and masticatory performance were 107.0±23.7 and 48.2±16.3, respectively. The number of chewing strokes showed a significant negative correlation to the masticatory performance (ρ=-0.767, p<0.0001). Conclusion: It was suggested that a color-changeable chewing gum might be useful to measure masticatory performance of complete denture wearers.